Fully-conformable porous polyethylene nanofilm sweat sensor for sports fatigue - Oktavius, A. K.; Gu, Q.; Wihardjo, N.; Winata, O.; Sunanto, S. W.; Li, J.; Gao, P. (IEEE Sensors Journal, 2021)
Wearable biosensors are considered to be a promising technology that revolutionizes conventional health monitoring methods as it is able to provide precautions when potential health problem is detected. However, the current fatigue-monitoring methods are still using either invasive blood tests or bulky inconvenient devices. Herein, we present a new skin patch sensor based on porous Ultra-High-Molecular-Weight Polyethylene (UHMWPE) nanomembranes which tracks muscle fatigue through sweat biomarkers, particularly cortisol hormone. By having nano-level thickness (i.e. around 100nm), the sweat sensor is able to conform perfectly to human skin without the necessity of any adhesives. We used Raman spectroscopy to analyze the sweat cortisol in the skin patch, established the calibration curve for both qualitative and quantitative characterization of sweat cortisol level change and validated the measurements with the blood samples collected at the same exercise intensity. From our experimental data, it is concluded that the cortisol level increases as the exercise intensity are increased and a strong correlation between the sweat cortisol and blood cortisol has been proven, demonstrating the patch's ability to detect sweat cortisol which acts as a strong indicator of sports fatigue level. Our developed UHMWPE membrane opens up a large opportunity for developing a one-of-a-kind sweat sensor by further integrating it with flexible electronics for signal processing and real-time transmission in future work.